2011
DOI: 10.1590/s0103-05822011000400016
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de métodos contraceptivos por adolescentes do sexo feminino da Comunidade Restinga e Extremo Sul

Abstract: Objective: To estimate the prevalence of contraceptives use among female adolescents and to describe their demographic and socioeconomic characteristics.Methods: Cross-sectional study carried out at the Community Management District "Restinga/Extremo Sul", in Porto Alegre, Southern Brazil, from July to December 2009. The sample included 487 adolescents aged ten to 19 years old, who live in this community. The main outcome was the use of contraceptive method alone or in association whit other methods; independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
1
1
0
8
Order By: Relevance
“…Similarly to the findings in literature, there was no significant association between the use of a birth control method and the analysed demographic and socioeconomic variables (6) . However, there was a greater social and economic vulnerability among the respondents, such as low individual income, a predominance of low education, and the performance of work activities that require minimal professional training (manicure, farmer and salesperson).…”
Section: Characterisation Of Userssupporting
confidence: 85%
“…Similarly to the findings in literature, there was no significant association between the use of a birth control method and the analysed demographic and socioeconomic variables (6) . However, there was a greater social and economic vulnerability among the respondents, such as low individual income, a predominance of low education, and the performance of work activities that require minimal professional training (manicure, farmer and salesperson).…”
Section: Characterisation Of Userssupporting
confidence: 85%
“…A population-based study in two health districts in the city of Porto Alegre, Rio Grande do Sul State, in 2009 found that 75% of sexually active females 10 to 19 years of age used some method. Of these, 61.8% used the pill and 38.2% male condoms 9 . The national school-based survey ERICA (Cardiovascular Risk in Adolescents) in 2013-2014 found that in sexually initiated boys and girls 12 to 17 years of age (n = 22,241), 80.3% of the boys and 85.2% of the girls reported having used some contraceptive method in their last sexual relations 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Antes de engravidar a minoria utilizava algum método contraceptivo de modo correto e eficaz, após a gravidez houve aumento no número de adolescentes que passou a utilizar pílula anticoncepcional e a injeção anticoncepcional, de modo contínuo e adequado. Um estudo realizado com 487 adolescentes em Porto Alegre, RS, mostrou que das adolescentes que tinham vida sexual ativa, 75% referiam uso de algum método contraceptivo, em sua maioria (61,8%) a pílula anticoncepcional (17) .…”
Section: Metodologiaunclassified